Runoff and Evapotranspiration–Precipitation Ratios as Indicators of Water Regulation Ecosystem Services in Urban Forests - Urša Vilhar (Land)
As a form of green infrastructure, urban forests play a key role in the provision of hydrological ecosystem services (ESs) in cities. Understanding how urban forest structure and soil properties influence water regulation ESs is crucial for managing and planning green infrastructure in cities. We analysed two indicators—the runoff to precipitation (Q/P) and the evapotranspiration to precipitation (ETP/P) ratios—for five different urban forests. We used the hydrological model Brook90 over 16 years to simulate runoff, evapotranspiration, canopy interception, transpiration and soil evaporation. The results showed that mixed forests have the highest water retention capacity, with the lowest Q/P (0.41) and the highest ETP/P (0.59). In contrast, riparian deciduous forests had the lowest water retention capacity, with the highest Q/P (0.75) and the lowest ETP/P (0.25). Both indicators showed similar annual and seasonal results. However, Q/P showed strong inter-annual variation and a strong correlation with precipitation, while ETP/P remained consistent despite precipitation fluctuations in the observed years. In conclusion, the ETP/P ratio is better suited to assess the water regulation ES of urban forests.